Liver involvement in patients with brucellosis: results of the Marmara study - Ozturk-Engin, D.; Erdem, H.; Gencer, S.; Kaya, S.; Baran, A. I.; Batirel, A.; Ormeci, N. (Springer, 2014)
Brucellosis is a zoonotic disease that primarily affects the reticuloendothelial system. But, the extent of liver damage in due course of the disease is unclear. This study included 325 brucellosis patients with significant hepatobiliary involvement identified with microbiological analyses from 30 centers between 2000 and 2013. The patients with a parts per thousand yen5 times of the upper limit of normal for aminotransferases, total bilirubin level a parts per thousand yen2 mg/dl or local liver lesions were enrolled. Clinical hepatitis was detected in 284 patients (87.3 %) and cholestasis was detected in 215 (66.1 %) patients. Fatigue (91 %), fever (86 %), sweating (83 %), arthralgia (79 %), and lack of appetite (79 %) were the major symptoms. Laboratory tests showed anemia in 169 (52 %), thrombocytopenia in 117 (36 %), leukopenia in 81 (25 %), pancytopenia in 42 (13 %), and leukocytosis in 20 (6 %) patients. The most commonly used antibiotic combinations were doxycycline plus an aminoglycoside (n = 73), doxycycline plus rifampicin (n = 71), doxycycline plus rifampicin and an aminoglycoside (n = 27). The duration of ALT normalization differed significantly in three treatment groups (p < 0.001). The use of doxycycline and an aminoglycoside in clinical hepatitis showed better results compared to doxycycline and rifampicin or rifampicin, aminoglycoside, doxycycline regimens (p < 0.05). However, the length of hospital stay did not differ significantly between these three combinations (p > 0.05). During the follow-up, treatment failure occurred in four patients (1 %) and relapse was seen in three patients (0.9 %). Mortality was not observed. Hepatobiliary involvement in brucellosis has a benign course with suitable antibiotics and the use of doxycycline and an aminoglycoside regimen seems a better strategy in select patients.
Keywords: Hepatitis; Metaanalysis; Experience; Efficacy; Disease